(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Use of an information system in Business organizations has become a necessity to survive for a long term in the business. As we know today an organization is making huge profits due to introduction of new products or product lines, but proper investment in R & D, Quality Systems and an organization wide Information system is must for a firm for long term survival. Along with other information system implementation of Marketing Information System has become quite common in case of Consumer Product Manufacturers. But in case or Industrial Products, Marketing Information System is not yet formalized or not considered important by many business firms. Due to stiff competition, dynamic marketing environment in Industrial Marketing, a business organization cannot afford to neglect the importance of Marketing Information System. This work is an effort to show the advantages of developing a Marketing Information System in the organizations manufacturing & selling Industrial Products/Services.